Uncovering nesfatin-1 and irisin hormones in schizophrenia and psychosis patients: A comparative investigation - Erhan Dinçer; Sermin Algul; Oguz Ozcelik (Biomarkers in Neuropsychiatry)
Objective: This study aims to elucidate the potential roles of the hormones nesfatin-1 and irisin in the pathophysiology of schizophrenia and psychosis. Methods: The study involved 80 participants, divided into three groups: schizophrenia (n=30), psychosis (n=20), and controls (n=30). Blood samples were collected from these participants, and the levels of irisin and nesfatin-1 were measured using the ELISA method. Results: The findings revealed that nesfatin-1 levels in schizophrenia patients were significantly higher compared to those in psychosis patients and controls. Additionally, nesfatin-1 levels in psychosis patients were significantly higher than in controls. In contrast, irisin levels were significantly lower in schizophrenia patients compared to both psychosis patients and controls. Discussion: These results suggest that nesfatin-1 and irisin may have important implications for understanding and treating schizophrenia and psychosis. Further research is needed to explore the roles of these hormones in the etiology, diagnosis, and treatment of these conditions.